2016
DOI: 10.1093/cid/ciw519
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi Sarcoma Risk in HIV-Infected Children and Adolescents on Combination Antiretroviral Therapy From Sub-Saharan Africa, Europe, and Asia

Abstract: HIV-infected children from SSA but not those from other regions, have a high risk of developing KS after cART initiation. Early cART initiation in these children might reduce KS risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This problem was addressed in a recent multiregional cohort study that directly compared the risk of developing KS in children starting cART in different geographic regions. Of the 24,991 HIV-infected children from Eastern Africa, Southern Africa and Europe starting cART, 26 children developed incident KS [15]. The study showed that KS (caused by an infection with Human Herpes Virus 8 (HHV-8)), is a frequent cancer in sub-Saharan Africa (SSA) and in SSA migrants in Europe, but cases are rare in children outside of this regions.…”
Section: Epidemiology Of Cancer In Hiv-infected Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem was addressed in a recent multiregional cohort study that directly compared the risk of developing KS in children starting cART in different geographic regions. Of the 24,991 HIV-infected children from Eastern Africa, Southern Africa and Europe starting cART, 26 children developed incident KS [15]. The study showed that KS (caused by an infection with Human Herpes Virus 8 (HHV-8)), is a frequent cancer in sub-Saharan Africa (SSA) and in SSA migrants in Europe, but cases are rare in children outside of this regions.…”
Section: Epidemiology Of Cancer In Hiv-infected Childrenmentioning
confidence: 99%
“…Kaposi Sarcoma incidence rates per 100,000 person-years with 95% confidence intervals, adapted from [15]…”
Section: Figurementioning
confidence: 99%
“…The overwhelming prevalence of HIV in a region where HHV-8 is endemic explains the staggering discrepancy in KS incidence in HIV-infected children globally. 11 In the pre-antiretroviral therapy (ART) era in the US and Europe, there were merely 14 cases of childhood KS reported over a 20-year span of multiple HIV-cancer registries. 12 17 In comparison, several reports describing relatively large cohorts of children and adolescents with KS in sub-Saharan Africa have been published in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most frequent cancers in AYALHIV are, depending on geographic region, Kaposi sarcoma (KS), non-Hodgkin lymphoma (NHL) and leiomyosarcoma [4,911]. KS is associated with Human Herpes virus 8 (HHV-8) infection; leiomyosarcoma and some NHL subtypes - with Epstein Barr virus (EBV) infection [12,13].…”
Section: Introductionmentioning
confidence: 99%